Prioritising health information needs in Europe: a Policy Delphi survey. (30th September 2020) - Seeling, S; Thißen, M; Achterberg, P; Carle, F; Lyons, R; Van Oyen, H; Tijhuis, M; Unim, B; Zelviene, A; Fehr, A
Abstract: Background: Health information (HI) includes data on population health, health determinants, health care systems, and health-relevant policy developments. Duly prioritised HI is essential to inform decision-makers, researchers and the public. Little can be found in the literature on HI prioritisation methods and procedures in Europe. Our study aims to close this gap. Methods: We designed a two-round online Policy Delphi and addressed 119 contacts, mainly public health and health information experts, in 33 InfAct partner countries. The first round included structured and full-text questions; in the ongoing second round, participants rank prioritisation approaches according to 'desirability', 'feasibility', 'importance' and 'confidence'. Results: In the first round, 19 questionnaires were fully completed; the presented results also include replies from interrupted surveys and drop-outs. 58% of the participants reported the existence of structured national HI prioritisation processes; 65% indicated stakeholder involvement, and 54% the application of defined criteria. National health targets or strategies played a major role in HI prioritisation. 17 respondents from 13 countries agreed to participate in the second round. Based on analysis of the first round, participants rank approaches to HI prioritisation, preferences for stakeholder involvement and coordination, partners and methods for criteria development, the role of national and international frameworks and options for good-practices in HI development. The expected outcome of our study is not one single recommendation for HI prioritisation, but a list of good practice-approaches. Conclusions: Health systems in Europe are heterogeneous, and so are health information systems. Mapping, sharing and ranking HI prioritisation approaches will facilitate knowledge exchange in the context of building a sustainable EU HI-system and may inform relevant EU processes.